Barriers for cancer clinical trial enrollment: A qualitative study of the perspectives of healthcare providers - Gaurav Kumar; Priyanka Chaudhary; Aiden Quinn; Dejun Su (Contemporary Clinical Trials Communications, 2022)
Background: Barriers to clinical trial enrollment have been the subject of extensive research; however, the rate of clinical trial participation has not improved significantly over time. Studies often emphasize patient-related barriers, but institutional and organizational barriers in the health care system may have a more substantial impact on clinical trial participation. Objective: To qualitatively identify perceived barriers to clinical trial participation based on perspectives from healthcare providers. Design: Qualitative research design with a phenomenological approach was used. A purposive sample of 18 healthcare providers participated in an in-depth focus group session. Participants were involved in cancer care and clinical research from a large hospital in the United States Midwest region. Data were transcribed, coded, and systematically analyzed through thematic content analysis. Results: The data revealed four levels of barriers to clinical trial enrollment, with emergent themes within each level: patient (beliefs or trust, distance to trial sites, health insurance coverage, language, and immigration status), provider (limited awareness of trial, time constraint, and non-cooperation from colleagues), clinical (eligibility criteria and clinical design), and institutional (policy and limited logistic support). Conclusion: Healthcare providers face complex, multifaceted, and interrelated barriers to clinical trial enrollment. To overcome these barriers, health care organizations need to commit more human and financial resources, break down boundaries for more efficient inter-departmental cooperation, develop more coordinated efforts in promoting trial awareness and participation, and remove unnecessary regulatory barriers.